Lulesia umbrinomarginata (Entolomataceae, Agaricales), a newly discovered species from Southern China - Xiao, Ying-Qun; Xu, You-Di; Chen, Zuo-Hong; He, Zheng-Mi (Phytotaxa, 2024)
The current study presents a new Lulesia species, namely L. umbrinomarginata, based on morphological and phylogenetic evidence. The analysis of five-locus dataset (ITS, LSU, RPB2, TEF1, and ATP6) suggests that it belongs to Lulesia subgenus Lulesia. It is distinguished by its clitocyboid basidiome, featuring a greyish brown to wood brown pileus with a darker involute margin, a depressed center and a positive red reaction to KOH, pale yellow-brown decurrent lamellae, a whitish, slightly eccentric stipe that darkens near the apex, an irregular lamellar trama, broadly ellipsoid angular basidiospores ornamented with undulating pustules, and the absence of clamp connections.